Examination of Strength Modeling Reliability of Physical Tests on Structural Concrete Columns - Sher Ali Mirza (Advances in Civil Engineering)
Comparisons and analyses of strengths from selected computational procedures were undertaken of more than 500 physical tests of rectangular, tied, structural concrete columns reported in the published literature. The computational procedures compared with the physical tests and with each other include a commercially available nonlinear finite element modeling software and the Canadian Standards Association (CSA) Standard A23.3-04. The requirements of the American Concrete Institute (ACI) 318-08 are very similar to those of the CSA A23.3-04, and hence, strength comparisons and analyses reported here are also applicable to ACI 318-08. The physical tests used for comparison were conducted on columns that were braced and pinned at both ends and were constructed using normal-density concrete with a compressive strength between approximately 17 and 57 MPa. The columns were subjected to short-term loads producing pure axial force, axial force combined with symmetrical single-curvature bending, or pure bending. Major variables included the concrete strength, the end eccentricity ratio, the slenderness ratio, the longitudinal reinforcing steel index for reinforced concrete or the structural steel index for composite columns, and the transverse reinforcement (tie/hoop) volumetric ratio. The study provides an examination of the reliability of the computational methods examined.